Effects of Warming and Phosphorus Enrichment on the C:N:P Stoichiometry of Potamogeton crispus Organs - Dai, Mingzhe; Wang, Tao; Wang, Yuyu; Xu, Jun (Frontiers in Plant Science, 2022)
The loss of submerged macrophytes from freshwater ecosystems is accelerating owing to the combined effects of eutrophication and climate change. Submerged macrophytes depend on spring clear water; however, increased water temperatures and excessive phosphorus (P) inputs often lead to the dominance of phytoplankton. It is still not clear how the stoichiometric characteristics of carbon (C), nitrogen (N), and P in different tissues of submerged macrophytes respond to P enrichment and temperature increases. In this study, we established 36 mesocosm ecosystems to explore the effects of warming and P addition on the leaf, turion, stem, and seed stoichiometry of Potamogeton crispus. The results revealed that different functional plant organs show distinct responses to P addition and warming, demonstrating the importance of evaluating the responses of different submerged macrophyte organs to environmental changes. In addition, interactive effects between P addition and warming were observed in the leaf, turion, and seed C:N:P stoichiometry, highlighting the importance of multifactorial studies. Our data showed that warming caused a decrease in the C content in most organs, with the exception of the stem; P addition increased the P content in most organs, with the exception of seed; and N content in the turion and seed were influenced by interactive effects. Collectively, P addition could help P. crispus to resist the adverse effects of high temperatures by aiding growth and asexual reproduction, and asexual propagules were found to be more sensitive to P enrichment than sexual propagules.